Clinical repercussions of neonatal ictericua in the premature (Research, Society and Development, 2021)
Objective: To analyze the possible clinical repercussions and their consequences in premature newborns affected by neonatal jaundice. Methodology: This is a narrative review using the PubMed and BVS data libraries, which included articles in Portuguese, English and Spanish, from 2010 to 2021. Results: Prematurity is one of the biggest causes of neonatal mortality, contributing to the increase of the infant mortality coefficient. Jaundice is one of the problems that most affect newborns, being defined by serum concentration of indirect bilirubin (BI) or direct bilirubin (BD) >1.5 mg/dL. One of the biggest complications of Neonatal Jaundice is Kernicterus, a bilirubin encephalopathy, a syndrome that causes neurological malfunction caused by the excess of unconjugated bilirubin in the bloodstream. The nursing team is responsible for receiving and preparing the NB for the treatment of Neonatal Jaundice, in addition to preparing the devices that will be used for phototherapy, such as the light spot and the incubator. Final Considerations: Despite being considered quite common, the clinical signs of jaundice should not go unnoticed, especially in premature infants, as the consequences of negligence in treatment can lead them to acquire a severe neurological syndrome.